Scope Creep Monitors Level of Satisfaction, Cost of Business and Slippery Slope Relationships Among Stakeholders, Project Manager, Sponsor and PMO to Execute Project Completion Report - Farok, G. M. G.; Garcia, Jose A. (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2016)
Scope creep is a change which is an update or addition to the whole or a part of project has been requested when the project is running on significantly an underway. Scope creep increases work with level of satisfactions off as well as any one would expect, but over time the project seems to get bigger and bigger while his or her price remains the same. The stakeholder either seems to think that the “extra work” is within the scope of the original agreement, or simply doesn’t realize that he or she is asking for more than was originally agreed. Either way, the project is losing money. Scope creep is a slippery slope and can be difficult to recover from. Once project manager accepts scope creep from one client s/ he is setting a precedent for the rest, and although s/ he may not have to physically hand over money as a result of scope creep, the effect is essentially the same. More time spent on a project than sponsor anticipated puts s/ he out of pocket.